Potential mouse models of coronavirus-related immune injury - Fu-Yao Nan; Cai-Jun Wu; Cai-Jun Wu; Jia-Hui Su; Lin-Qin Ma; Lin-Qin Ma (Frontiers in Immunology, 2022)
Basic research for prevention and treatment of coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), continues worldwide. In particular, multiple newly reported cases of autoimmune-related diseases after COVID-19 require further research on coronavirus-related immune injury. However, owing to the strong infectivity of SARS-CoV-2 and the high mortality rate, it is difficult to perform relevant research in humans. Here, we reviewed animal models, specifically mice with coronavirus-related immune disorders and immune damage, considering aspects of coronavirus replacement, viral modification, spike protein, and gene fragments. The evaluation of mouse models of coronavirus-related immune injury may help establish a standardised animal model that could be employed in various areas of research, such as disease occurrence and development processes, vaccine effectiveness assessment, and treatments for coronavirus-related immune disorders. COVID-19 is a complex disease and animal models cannot comprehensively summarise the disease process. The application of genetic technology may change this status.